Distinctive characteristics of collagen and gelatin extracted from Dosidicus gigas skin. (24th January 2021) - Sun, Bolun; Li, Chao; Mao, Yuhong; Qiao, Zhaohui; Jia, Ru; Huang, Tao; Xu, Dalun; Yang, Wenge
Summary: Squid skin, often discarded as processing by‐product, is a good resource of collagen/gelatin. In this study, acid soluble collagen (ASC), pepsin soluble collagen (PSC) and water soluble gelatin (WSG) were extracted from squid ( Dosidicus gigas ) skin and physicochemically examined. The lowest yield of 33.5% was obtained for ASC extracted at 4 °C, and the addition of pepsin increased the collagen yield by around 35.0% (PSC). The highest yield of 81.9% (WSG) was achieved by thermal extraction at 60 °C. A low temperature can largely retain the native helix structures of ASC and PSC, contrariwise, thermal treatment converted collagen into gelatin with unordered and renatured structures. The proline and hydroxyproline contents of ASC, PSC and WSG were 183/1000 residues, 194/1000 residues and 175/1000 residues, respectively. In addition, WSG showed a denaturation temperature at 80.7 °C which was much higher than that of ASC (24.2 °C) and PSC (26.2 °C), while a significant lower resistance towards enzymatic digestion. Abstract : Comprehensive analysis of physiochemical, structural properties, and protein digestibility of collagen and gelatin extracted from the squid ( Dosidicus gigas ) skin.